2003
DOI: 10.1007/s00464-002-8768-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinical application of semi-loop-shaped retractor for gasless laparoscopic surgery

Abstract: This new retractor for gasless laparoscopic surgery provides good exposure and has the potential to enhance the performance of advanced laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Different instruments and techniques have been used in order to accomplish the gasless space away from the potential side effects of pneumoperitoneum and the insufflation of CO 2 such as: Laparolift™ and laparofan, 27 Laparotenser® device, 28,29 traction on straight metal rods, 30 traction on Foley's catheter, 31 the use of a semi-loop-shaped abdominal retractor 32 and the use of towel clips with a ceilingmounted laplift. 33 Some of these instruments are complex, expensive and are not available in all hospitals; others are tedious to mount and assemble with loss of extra time or need extra stab wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Different instruments and techniques have been used in order to accomplish the gasless space away from the potential side effects of pneumoperitoneum and the insufflation of CO 2 such as: Laparolift™ and laparofan, 27 Laparotenser® device, 28,29 traction on straight metal rods, 30 traction on Foley's catheter, 31 the use of a semi-loop-shaped abdominal retractor 32 and the use of towel clips with a ceilingmounted laplift. 33 Some of these instruments are complex, expensive and are not available in all hospitals; others are tedious to mount and assemble with loss of extra time or need extra stab wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that for an “average” adult patient, the radius of the retractor should be 8.5 cm. 11 However, to achieve optimal exposure in patients of many ages and sizes, retractors of different sizes will be needed. Therefore, a retrospective study was developed to collect cross-sectional computed tomography (CT) data from subjects varying in age and weight.…”
Section: Methodsmentioning
confidence: 99%
“…When several anchoring points are used, this reduces the maneuvering space of the laparoscopist and increases the number of incision sites for the patient. 4,9,11-15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides decreasing the pneumoperitoneum pressure, there are techniques for abdominal wall lift so that pneumoperitoneum pressure can be greatly deceased during MIS. 15,16 These involve a retractor system that helps to lift the abdominal wall with assistance from outside the patient, rather than intra-abdominal pressure pushing out uniformly from within the abdomen. Running a brief test in severe Trendelenburg position before prepping will sometimes identify the occasional patient that simply can't tolerate this position for very long.…”
Section: Special Patient Populationsmentioning
confidence: 99%